The Model of Simultaneous General Elections in Order To Realize Democratic Elections: Analytical Study of The Decision of The Constitutional Court No. 55/PUU-XVII/2019 - Nuri Vina Mawaddah; Tunggul Anshari S. N; Dhia Al Uyun (Journal of Science and Education (JSE), 2025)
This research aims to analyse the implementation of the 2019 simultaneous general elections (elections), which actually caused various problems in practice. Responding to these dynamics, the Association for Elections and Democracy (Perludem) submitted a judicial review of the Election Law to the Constitutional Court, which then resulted in Constitutional Court Decision Number 55/PUU-XVII/2019 . This research is based on two main questions. First, how is the simultaneous general election model as stated in the Constitutional Court Decision Number 55/PUU-XVII/2019 analysed in terms of the basic principles of democratic elections? Second, how is the ideal simultaneous general election model after the Constitutional Court Decision Number 55/PUU-XVII/2019 In answering these questions, this research is supported by normative legal research methods (doctrinal) with three approaches, namely the legislative approach, conceptual approach, and historical approach analysed prescriptively analytically. Based on the results of the research and analysis conducted, the following conclusions were drawn: First, with the birth of Constitutional Court Decision No. 55/PUU-XVII/2019 6 variants of the simultaneous election model. In the analysis used, the constitutional judges used historical interpretation and functional interpretation methods in deciding the constitutional simultaneous election model. Second, Constitutional Court Decision Number 55/PUU-XVII/2019 affirms the significance of Constitutional Court Decision Number 14/PUU-XI/2013 in the context of simultaneous general election arrangements. The idea of holding elections with five ballot boxes is actually not the only model that has developed in the discourse on amending the 1945 Constitution of the Republic of Indonesia. The Constitutional Court has explicitly formulated six alternative models of simultaneous elections that are considered to remain in line with constitutional principles. Among these alternatives, the fourth model is considered the most ideal to be implemented in the future simultaneous election system, given its conformity with the principles of effectiveness, efficiency and accountability in organising democratic elections.